CONTAMINATION OF Pb, Cd, Cu, Zn IN BLACK POMFRET (Formio niger) AND TONGUE SAND (Cynoglossus lingua) FISH CAUGHT FROM THE WESTERN PART OF MADURA STRAIT AND ITS SAFE LIMITS CONSUMPTION - Acivrida Mega Charisma; Bambang Irawan; Agoes Soegianto (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2013)
Contamination of Pb, Cd, Cu, Zn in the flesh on the two types of fish consisting pelagic fish include Black pomfert (Formio niger) whereas among other demersal fish include Tongue sand (Cynoglossus lingua), was conducted in March-December 2013, which was taken from the western part of Madura Strait (Gresik-Ujung pangkah, Surabaya-Kenjeran, and Sidoarjo-Sedati). Pb, Cd, Cu, and Zn detected using AAS (Atomic Absorption Spectrometry) brand Shimadzu AA-6200. The highest content of heavy metals, namely Pb in Cynoglossus lingua from the Sedati (5.63ppm±0.05), while a low of Cd in Formio niger from the Ujung pangkah (0.20ppm±0.004). The results show that there is a correlation between heavy metal with fish but not significantly. The content of Pb, Cd, Cu, Zn in 2 fish species originating from all locations stated below the exposure limits for consumption. Safe limit fish consumption of Formio niger is based on the WHO PTWI of 347.43 grams / week and Cynoglossus lingua 191.25 grams / week.